Evaporation characteristics of ethanol droplets containing graphite nanoparticles under infrared radiation. (November 2017) - Tanvir, Saad; Biswas, Sayan; Qiao, Li
Highlights: The evaporation behavior of nanofluids are not well understood and there are inconsistency in the literature regarding the effect of nanoparticle addition on the evaporation rate of the base fluid. Additionally, very few papers have examined the effect of radiation on the evaporation behavior of nanofluids, which however have potential applications in several areas such as combustion of nanofluid fuels and solar energy harvesting using nanofluids. In the present paper, the evaporation characteristics of liquid ethanol droplets containing graphite nanoparticles under infrared radiation were studied both experimentally and numerically. Particularly, a model was developed to simulate the instantaneous evaporation rate of the nanofluid droplet, considering both effects of particle motion and accumulation on droplet surface and radiation absorption by the nanoparticles. A stochastic Monte Carlo method was used to track photon penetration into the nanofluid droplet and thus determine the distribution of the absorbed radiation energy. The combined experimental and modeling results show that two competing mechanisms control the instantaneous evaporation rate. In the early stage of evaporation, radiation absorption by the nanoparticles near the droplet surface increases the surface temperature and thus enhance evaporation. At the later stage of evaporation, however, this effect is suppressed by the reduced effective surface area for evaporation due to particle accumulation at the droplet surface. As a result, the evaporation rate decreases. Abstract: The evaporation characteristics of liquid ethanol droplets containing graphite nanoparticles under infrared radiation were studied both experimentally and numerically. The experimental results show that the droplet evaporation rate is higher in the presence of a 2 mW infrared radiation field with a fixed wavelength of 2.3 μm than without radiation. The evaporation rate, however, decreases over time. Additionally, with particle addition, the evaporation rate no longer follows the classical D 2 -law. The deviation is greater at higher particle concentrations. A model was developed to simulate the instantaneous evaporation rate, considering both effects of particle accumulation on the droplet surface and radiation energy absorption by the nanoparticles. In particular, a stochastic Monte Carlo method coupled with Mie theory and Beer–Lambert law of volumetric absorption was used to calculate the distribution of the absorbed radiation energy within the droplet, which was then used to compute the temperature profiles of the droplet. The modeling results show under infrared radiation, the evaporation rate of the nanofluid droplet increases as a function of particle concentration. This is due to rising droplet surface temperature through radiation absorption by the nanoparticles near the droplet surface. However, at the later stage of evaporation, as the particles start to accumulate on the droplet surface, the effective surface area for evaporation decreases and hence reduces the evaporation rate. These two competing mechanisms combine to control the instantaneous evaporation rate.